S60 Non-invasive measurement of lung inhomogeneity following recovery from primary spontaneous pneumothorax. (December 2018) - Hallifax, RJ; Smith, NMJ; Talbot, NP; Petousi, N; Ritchie, GAD; Rahman, NM; Robbins, PA
Abstract : Background: There is some evidence that patients with Primary Spontaneous Pneumothorax (PSP) have subtle emphysema-like change (ELC) and regional airway inflammation. These abnormalities may not be evident using standard lung function testing. We hypothesized that a novel non-invasive method for quantifying lung inhomogeneity (LI) would reveal lung abnormalities in patients following PSP. Methods: Twelve patients were enrolled following PSP, along with 25 healthy volunteers. All participants gave written informed consent and each underwent a standard nitrogen washout test (10 min breathing air, 5 min breathing O2 ), using a novel gas analyser that precisely measures respired gases using laser absorption spectroscopy. A mathematical model of the lung was fitted to the data to estimate LI parameters, including the distribution of lung compliance relative to alveolar volume (&x03C3;CL:VA). 1 Results: The PSP and healthy volunteer groups were well-matched for age (29.8±8.4 vs 26.4±7.3 years, mean ±SD, respectively) and height (181±9 vs 179±7 cm). In the pneumothorax group, five patients were smokers (four current and one former; mean 9±4 pack years). In the healthy group, all participants were never-smokers. In the PSP group as a whole, &x03C3;CL:VA was significantly elevated, compared with healthy volunteers (p<0.03, Student's t-test). However, further analysis (ANOVA) revealed that the elevation in &x03C3;CL:VA was due to the effects of smoking history (p<0.001), with no significant independent effect of pneumothorax status (p>0.4; figure 1A). The former smoker had the lowest value for &x03C3;CL:VA in the smoker group. Importantly, despite the clear effect of smoking on &x03C3;CL:VA within the PSP group, neither smoking history (p>0.3) nor pneumothorax status (p>0.1) had any significant effect on forced expiratory volume in 1 s (FEV1 ), the standard method of detecting airways disease (figure 1B). Conclusion: This study shows that it is possible to demonstrate statistical differences in LI between a small group of PSP patients and controls, mainly due to modest smoking history in the PSP group. However, such differences were not apparent using FEV1 . Although controls were not matched for age or smoking, this study nevertheless suggests that measures of LI may provide a sensitive method for exploring possible parenchymal abnormalities. Reference: Mountain et al . doi.org/10.1152/japplphysiol.00745.2017